The Malaysia-Japan model on technology partnership international proceedings 2013 of Malaysia-Japan Academic Scholar Conference - Ab. Hamid Khairuddin; Ono, Osamu; Bostamam, Anas M.; Ling, Amy Poh Ai (Springer Japan, 2015)
The selected papers included in this proceedings on Malaysia-Japan Academic Scholar Conference (MJASC) 2013, are related to nano-science engineering, mechanical engineering, electrical and electronic engineering, computer science, information technology etc. This proceedings will be a source of research findings for Malaysia and Japan specifically, and other countries in general, especially among researchers, industry sectors and government policy makers. It will be served as a resourceful reference and platform to reflect the significant of the Look East Policy outcomes and products.